THE MEMES OF HADITH ON DOWRY IN SOCIAL MEDIA: Paul Ricoeur’s Hermeneutical Perspective - Taufiqotuzzahro', 'Azzah Nurin; Ja'far, Ali; Alawy, Muhammad Syihabudin (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
Abstract: This study examines how people understand and convey the message of a hadith about dowries through memes, using images and illustrations. By analyzing these memes hermeneutically, particularly those shared on social media, the research explores the interplay of image, caption, underlying ideas, and how the hadith is interpreted. Conducted as library research, it employs descriptive analysis methods and a hermeneutic approach, focusing on a meme about marriage dowries sourced from a Facebook fan page. Paul Ricoeur’s hermeneutics framework guides the analysis. The findings reveal that hadith memes reflect the social construction of society based on real-life experiences. These constructions promote the idea of a “salehah” (pious) woman as someone who requests a modest dowry. The interpretation of the meme’s content serves as a symbol for readers, conveying the hadith’s message in informative, declarative, interjective, and affirmative ways. Furthermore, the study highlights that women who do not conform to or uphold the hadith’s teachings may face a negative social image.Keywords: Memes, Hadiths, Dowry, Hermeneutics, Labeling